Sensor Signal-based Learning Improvement Framework for Intellectually Disabled (ID) Child Education (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
According to World Health Organization (WHO), persons with cognitive impairments such as dementia, aphasia and development disorders account around 1.25% of world population. Specifically, there are 31 million individuals including 35.29% children with Intellectual Disabilities (ID) in India. Only 1% of these children have access to school and majority of them fail to express their needs and thoughts in classrooms. Their learning skills can be enhanced by incorporating wireless sensors in Assistive Technologies (AT). Rapid growing signal-based wireless sensors with smart devices motivate the development of many learning methodologies for ID school Education. This paper aims to design, implement and evaluate an Alternative and Augmentative Communicate (AAC) system for ID school education by validating, utilizing and manifesting signal-based wireless sensors. This context-based AAC employs the Low Power Bluetooth (BLE) technology for the nonverbal interaction in class room teaching. The system utilizes the high indoor tracking accuracy of signal-based BLE beacons to acquire the effective context from backend application server and presents the symbols in smart devices.The children communicate with visual objects like apple at an appropriate time i.e. during lunch time by utilizing smart phone or tablet. The system incorporates the involvement of user management such as login and profile maintenance for teachers and caregivers through smart devices.